Preparation of three-dimensional compact graphene / manganese oxide composite material and application of three-dimensional compact graphene / manganese oxide composite material in electrochemical lithium storage performance research
Through the laminated structure of graphene and MnO particles composite, the problems of insufficient conductivity and serious volume expansion of manganese oxide electrode materials during circulation are solved, and electrode materials with high conductivity and cycle stability are achieved, suitable for lithium-ion batteries Negative electrode material.
Patent Information
- Application Number
- CN202411612007.9
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-11-13
- Publication Date
- 2025-02-18
- Estimated Expiration
- 2044-11-13
AI Technical Summary
The existing manganese oxide electrode materials lack conductivity and severe volume expansion during the charge and discharge cycle, resulting in structural instability and electrochemical performance decay.
A laminated structure (DG/MnO) is used to combine graphene and MnO particles. MnO particles are distributed in the middle of the graphene sheet layer, providing a stable migration channel, and graphene improves conductivity and buffers volume expansion.
It improves the conductivity and cycle stability of the electrode material, improves the electrochemical energy storage performance, and ensures the good performance of the electrode under high magnification and long cycle life.
Smart Images

Figure CN119480990A_ABST
Abstract
Description
Technical Field
[0002] The present invention relates to the field of material preparation and energy storage, and in particular to the preparation of a three-dimensional dense graphene / manganese oxide composite material and research on its electrochemical lithium storage performance. Background Art
[0003] The rapid development of portable electronic devices and electric vehicle markets has attracted widespread attention from researchers around the world to energy storage devices. Lithium-ion batteries have long been considered a promising electrochemical energy storage device. Transition metal oxides are often widely studied as negative electrode materials for lithium-ion batteries due to their superior capacity performance, safety, and price advantages. Among the many transition metal oxides, MnO materials have a high theoretical specific capacity (756 mAh g -1 ), lower hysteresis voltage (<0.8 V), larger density (5.43 g cm -3 ) and environmental friendliness, it is considered to be a potential negative electrode material for lithium-ion batteries. However, this material also has disadvantages such as poor conductivity, severe volume expansion during charge and discharge, and poor rate performance and cycle stability.
[0004] In order to solve the above problems, an effective strategy is to construct a composite material of manganese monoxide and carbon, using nanocarbon materials as a conductive network and buffering the volume expansion. Among them, carbon coating can greatly improve the conductivity and electrode polarization resistance of MnO electrode materials, thereby significantly improving the rate performance of the electrode. However, during the charge and discharge cycle, the huge volume expansion will cause the carbon coating layer in the active material to rupture, so the carbon coating technology still cannot meet the cycle stability requirements in actual production applications. Graphene, as a widely studied carbon material, can not only improve the conductivity of MnO, but also act as a buffer zone during the electrochemical cycle, thereby limiting the volume expansion of MnO particles. Unfortunately, after simple compounding, the MnO particles exposed on the graphene surface will still fragment and agglomerate during the charge and discharge process, resulting in the attenuation of the electrochemical performance of the electrode. Therefore, constructing a superior electrode structure that can not only improve the conductivity of manganese oxide composite materials but also provide a stable conductive network during the cycle has become a research focus.
[0005] In summary, the present invention prepares a composite laminated structure of graphene and MnO particles (DG / MnO). MnO particles are distributed in the middle of the wrinkled graphene sheets as a support, which can provide a stable and abundant migration channel for lithium ion migration. The graphene sheets can greatly improve the conductivity of the MnO particles and ensure the rapid transfer of charges. This tightly stacked structure is conducive to improving the transmission dynamics of electrons / ions, and enhancing the structural and interface stability during the charge and discharge process, so that it has excellent electrochemical energy storage performance and cycle stability, and has good application prospects as a negative electrode material for lithium-ion batteries. Summary of the invention
[0006] The purpose of the present invention is to design a method for preparing a negative electrode material for lithium-ion batteries that can improve the conductivity of the manganese oxide composite material and provide a stable conductive network during the cycle, thereby improving the specific capacity and cycle performance of the electrode material.
[0007] The present invention uses Na-doped manganese dioxide and graphene as raw materials to prepare a three-dimensional dense graphene / manganese oxide composite material, and the preparation method for applying it to the negative electrode of a lithium ion battery is carried out according to the following steps: 1. Room temperature synthesis of Na-doped manganese dioxide (MnO2-Na) Weigh 0~140 g of NaCl and dissolve it in 100 mL of deionized water. After vigorous stirring for 30 min, add 0.5 g of KMnO4 to the above solution and stir vigorously for 3 h. Then measure 75 mL of ethanol and slowly add it to the solution using a separatory funnel. Continue stirring for 30 min. After the reaction is completed, centrifuge and wash immediately until there is no Cl in the system. - (Silver nitrate was used for testing). After sonication, freeze drying was performed and the obtained sample was recorded as MnO2-Na-x (where x corresponds to the amount of NaCl added, in g). The MnO2-Na-x sample was prepared into a dispersion for later use; Preparation of two-dimensional and three-dimensional dense graphene manganese oxide (DG / MnO) 200 mL of GO suspension (0.5 mg / mL) was subjected to strong ultrasound for 10 min, and then ultrasonicated with 100 mL of MnO2 dispersion (containing about 120 mg~350 mg of MnO2) until completely dispersed. The above two dispersions were placed in a common ultrasonic water tank, and the MnO2 dispersion was added dropwise to the GO solution (about 5 min) and strongly ultrasonicated for 10 min. The liquid after ultrasonication was evaporated to dryness in a 45°C water bath until about 10 mL of slurry remained. The slurry was applied to a polyethylene plate and dried at room temperature to obtain GO / MnO2 flakes, which were calcined at 600~800°C in a hydrogen atmosphere for 2 h to obtain the sample.
[0008] Compared with the existing technology, the present invention has the following beneficial effects: (1) The present invention composites graphene and MnO particles to form a laminated structure (DG / MnO). MnO particles are distributed in the middle of the wrinkled graphene sheets as a support, which can provide a stable and abundant migration channel for lithium ion migration. The graphene sheets can greatly improve the conductivity of the MnO particles and ensure the rapid transfer of charges. This tightly stacked structure is conducive to improving the transmission dynamics of electrons / ions, and enhancing the structural and interface stability during the charge and discharge process, ensuring good conductivity and cycle stability of the electrode.
[0009] (2) In the graphene and MnO stacked structure (DG / MnO) prepared by the present invention, manganese monoxide particles are evenly and tightly distributed between graphene sheets. This dense stacked structure can effectively inhibit the structural collapse of the electrode material caused by ion transport and buffer the volume expansion of MnO during the charge and discharge process, which is beneficial to stabilizing the structural stability of the electrode material. BRIEF DESCRIPTION OF THE DRAWINGS
[0010] Figure 1 This is a microscopic morphology photo of a DG / MnO composite material prepared using Na-doped manganese dioxide and graphene as raw materials; Figure 2 The crystal structure and chemical composition of a DG / MnO composite material prepared using Na-doped manganese dioxide and graphene as raw materials; Figure 3 It is a DG / MnO composite material prepared with Na-doped manganese dioxide and graphene as raw materials and has good electrochemical performance; Figure 4 This is the morphology of DG / MnO composite material prepared with Na-doped manganese dioxide and graphene as raw materials. DETAILED DESCRIPTION
[0011] Specific implementation method 1: A three-dimensional dense graphene / manganese oxide composite material is prepared using Na-doped manganese dioxide and graphene as raw materials, and is applied to the negative electrode of a lithium-ion battery. The preparation method is carried out according to the following steps: 1. Room temperature synthesis of Na-doped manganese dioxide (MnO2-Na) Weigh 0~140 g of NaCl and dissolve it in 100 mL of deionized water. After vigorous stirring for 30 min, add 0.5 g of KMnO4 to the above solution and stir vigorously for 3 h. Then measure 75 mL of ethanol and slowly add it to the solution using a separatory funnel. Continue stirring for 30 min. After the reaction is completed, centrifuge and wash immediately until there is no Cl in the system. -(Silver nitrate was used for testing). After sonication, freeze drying was performed and the obtained sample was recorded as MnO2-Na-x (where x corresponds to the amount of NaCl added, in g). The MnO2-Na-x sample was prepared into a dispersion for later use; Preparation of two-dimensional and three-dimensional dense graphene manganese oxide (DG / MnO) 200 mL of GO suspension (0.5 mg / mL) was subjected to strong ultrasound for 10 min, and then ultrasonicated with 100 mL of MnO2 dispersion (containing about 120 mg~350 mg of MnO2) until completely dispersed. The above two dispersions were placed in a common ultrasonic water tank, and the MnO2 dispersion was added dropwise to the GO solution (about 5 min) and strongly ultrasonicated for 10 min. The liquid after ultrasonication was evaporated to dryness in a 45°C water bath until about 10 mL of slurry remained. The slurry was applied to a polyethylene plate and dried at room temperature to obtain GO / MnO2 flakes, which were calcined at 600~800°C in a hydrogen atmosphere for 2 h to obtain the sample.
[0012] Specific implementation method 2: A three-dimensional dense graphene / manganese oxide composite material is prepared using Na-doped manganese dioxide and graphene as raw materials, and is applied to the negative electrode of a lithium-ion battery. The preparation method is carried out according to the following steps: The difference between this embodiment and the first embodiment is that the content of NaCl in step 1 is 70 g. The rest is the same as the first embodiment.
[0013] Specific implementation method three: A three-dimensional dense graphene / manganese oxide composite material is prepared using Na-doped manganese dioxide and graphene as raw materials, and is applied to the negative electrode of a lithium-ion battery. The preparation method is carried out according to the following steps: The difference between this embodiment and the first embodiment is that the content of MnO2 used in step 2 is 175 mg. The rest is the same as the first embodiment.
[0014] Specific embodiment 4: A three-dimensional dense graphene / manganese oxide composite material is prepared using Na-doped manganese dioxide and graphene as raw materials, and is applied to the negative electrode of a lithium-ion battery. The preparation method is carried out according to the following steps: The present embodiment is different from the first embodiment in that the GO / MnO2 flakes prepared in step 2 are calcined at 700°C in a hydrogen atmosphere for 2 h to obtain DG / MnO-700. The rest is the same as the first embodiment.
[0015] The following test is used to verify the effect of the present invention: In this experiment, a three-dimensional dense graphene / manganese oxide composite material was prepared using Na-doped manganese dioxide and graphene as raw materials, and the preparation method for the negative electrode of a lithium-ion battery was carried out in the following steps: 1. Room temperature synthesis of Na-doped manganese dioxide (MnO2-Na) Weigh 70 g of NaCl and dissolve it in 100 mL of deionized water. After vigorous stirring for 30 min, add 0.5 g of KMnO4 to the above solution and stir vigorously for 3 h. Then measure 75 mL of ethanol and slowly add it to the solution using a separatory funnel. Continue stirring for 30 min. After the reaction is completed, centrifuge and wash immediately until there is no Cl in the system. - (Silver nitrate was used for testing). After ultrasonication, freeze drying was performed and the obtained sample was recorded as MnO2-Na-70. The MnO2-Na-70 sample was prepared into a dispersion for later use.
[0016] Preparation of two- and three-dimensional dense graphene manganese oxide (DG / MnO-700) 200 mL of GO suspension (0.5 mg / mL) was subjected to strong ultrasound for 10 min, and then to ultrasound with 100 mL of MnO2 dispersion (containing about 175 mg of MnO2) until completely dispersed. The two dispersions were placed in a common ultrasonic water tank, and the MnO2 dispersion was added dropwise to the GO solution (about 5 min) and strongly ultrasounded for 10 min. The liquid after ultrasound was evaporated to dryness in a 45°C water bath until about 10 mL of slurry remained. The slurry was applied to a polyethylene plate and dried at room temperature to obtain GO / MnO2 flakes, which were calcined at 700°C in a hydrogen atmosphere for 2 h to obtain sample DG / MnO-700.
[0017] Figure 1a shows the microscopic morphology of DG / MnO-700. It can be seen that the morphology of the DG / MnO-700 sample is a tightly stacked layered structure, and the manganese monoxide particles are evenly and tightly distributed between the graphene sheets. Among them, the graphene sheets can increase the overall conductivity of the electrode material, ensure the rapid migration of electrons in the electrode, and buffer the volume changes of manganese monoxide particles caused by the insertion and deinsertion of lithium ions during the charging and discharging process. Manganese monoxide particles can not only serve as active materials, but also as a supporting structure between sheets to prevent the restacking of graphene sheets during the charging and discharging process, and maintain the structural stability of the electrode and the integrity of the ion transmission channel. Moreover, this "sandwich" structure is conducive to the full contact between the electrolyte ions and the active material, improving the electrode wettability, the diffusion rate of the electrolyte ions and the effective specific surface area of the electrode material ( Figure 1 a). MnO particles are evenly distributed in the DG / MnO-700 material, and manganese monoxide can support the graphene sheet and provide more ion transmission channels ( Figure 1b, 1c). The graphene sheets are closely connected to MnO, ensuring the overall conductivity of the material. The wrinkles of the graphene sheets are obvious. This special structure can provide two typical interlayer ion transport channels, namely the ridge channels provided by the graphene wrinkles and the support channels provided by the MnO particles ( Figure 1 c). Transmission electron microscopy was used to further determine the internal microstructure and crystal structure of DG / MnO-700. It can be seen that MnO particles are evenly distributed on the graphene sheets. The particle size and distribution are consistent with those of SEM. Figure 1 The stacking structure of the material is obvious ( Figure 1 d), further confirming the dense stacking structure of DG / MnO-700. After analyzing the lattice fringes, it can be concluded that its lattice spacing is 0.26nm, corresponding to the (111) crystal plane of MnO (Figure 1e). The selected area electron diffraction spectrum of DG / MnO-700 shows a clear diffraction pattern that is consistent with manganese monoxide, indicating that MnO has good crystallinity (Figure 1f). The element distribution diagram of DG / MnO-700 shows that the C element is evenly distributed in the material, and the Mn and O elements are concentrated in the spherical area (Figure 1g).
[0018] Figure 2 The structure, chemical composition and valence state of DG / MnO-700. In Figure 2a, all samples show obvious characteristic peaks at 34.9˚, 40.5˚, 58.7˚, 70.2˚ and 73.8˚, corresponding to the (111), (200), (220), (311) and (222) crystal planes of cubic MnO, respectively, proving the existence of MnO (JCPDS NO. 07-0230). The broad peak near 26˚ corresponds to the C peak of graphene, indicating the existence of a densely packed graphene structure. The characteristic peak around 15.8˚ in the XRD spectrum of the MnO-700 sample corresponds to Na 0.7 MnO 2.05 The (002) crystal plane of the MnO sample indicates that the conversion is incomplete and trivalent manganese exists, which is consistent with the results observed by transmission electron microscopy and selected area electron diffraction. The Raman spectrum is shown in Figure 2b. At 602 cm -1The characteristic peak at 1340 cm-1 and 1596 cm-1 corresponds to the vibration of the Mn-O bond in MnO. It is worth noting that the characteristic peak of DG / MnO-700 due to the vibration of the Mn-O bond is significantly blue-shifted compared with MnO, which may indicate that there is a strong electronic coupling between MnO and graphene. This phenomenon often occurs when transition metal oxides are composited with carbon-based materials, confirming that MnO and graphene are effectively composited rather than simply physically mixed. Compared with MnO-700, the DG / MnO-700 and G / MnO-700 samples have a blue-shift at 1340 cm-1 and 1596 cm-1. -1The two characteristic peaks appearing at the 40°C correspond to the D peak and G peak of the carbon material, which confirms the presence of graphene in the material. The ratio of these two peaks (ID / IG) is often used to determine the number of defects in the microstructure of the carbon material. After calculation, the ID / IG values of DG / MnO-700 and G / MnO-700 are 0.974 and 0.893, respectively, indicating that the disordered structure and defective structure of DG / MnO-70 are relatively large, which is consistent with the TEM measurement results. The DG / MnO-700 composite material was subjected to thermogravimetric analysis under argon atmosphere, as shown in Figure 2 c. The decrease in mass of the DG / MnO-700 composite material from room temperature to 300°C corresponds to the reduced mass of adsorbed water and structural water escaping from the composite material. The mass change between 400 and 500°C is attributed to the gradual conversion of MnO to Mn2O3. After calculation, it can be obtained that the content of graphene in the DG / MnO-700 composite material is 33.8wt%. XPS test analysis was used to further confirm the elemental composition and valence state of manganese in the DG / MnO-700 composite material, as shown in Figure 2 d. Figure 2 d is the full XPS spectrum of the DG / MnO-700 composite material. From the XPS total spectrum, it can be seen that the DG / MnO-700 composite material contains four elements, C, Mn, O and Na, which is the same as the result of the elemental analysis diagram. From the Mn2p spectrum shown in Figure 2 e, it can be seen that two obvious characteristic peaks can be observed in the spectrum at binding energies of 653.7 and 641.8 eV, corresponding to Mn 2p1 / 2 and Mn 2p3 / 2 of Mn, respectively. The binding energy difference between the two characteristic peaks is 11.6 eV, which shows that the valence state of manganese is Mn (II), which is consistent with the XPS spectrum characteristics of manganese monoxide and is consistent with the XRD results. After fitting, Mn 2p3 / 2 consists of three characteristic peaks located at 644.0, 642.1 and 640.9 eV, the former corresponding to Mn (III) and the latter two corresponding to Mn (II). The content of Mn (III) in the sample can be estimated by the area of the fitting curve. After calculation, the content of Mn (III) in the sample is 29.7%. The presence of trivalent manganese ions in the sample is due to the presence of Mn 7+ To Mn 2+ The conversion is incomplete. In order to maintain electrical neutrality, cation vacancies appear in the manganese monoxide lattice. The appearance of such ion vacancies can improve the conductivity of the material, provide active sites for electrochemical reactions, and be more conducive to the transmission of electrolyte ions in the electrode material, which is beneficial to the electrochemical performance of the battery. According to the Mn2p spectrum of the MnO-700 sample in Figure 2i, the Mn in the MnO-700 sample is 3+The content is 45.3%, which is significantly higher than that of DG / MnO-700, indicating that the conversion of manganese monoxide in the MnO-700 sample is incomplete. The presence of carbon in the DG / MnO-700 sample makes it easier to reduce manganese ions to a lower valence state. 3+ In comparison, due to the 2+ It has a relatively lower Gibbs free energy and the most stable electron configuration in the outer orbital, so Mn 2+ It is difficult to spontaneously oxidize to Mn 3+ , MnO exists stably in the air. In the C1s spectrum, the peak at 284.8 eV is consistent with the characteristic peak of graphite carbon, while the peaks at 285.5, 288.1 and 291.5 eV correspond to C-OH, C=O and OC=O, respectively (Figure 2 f). In the O1s spectrum, the two peaks at 535.7 and 534.1 eV correspond to HOH and Mn-OH, respectively, while the strong fitting peak at the binding energy of 531.4 eV corresponds to Mn-O-Mn (Figure 2 g). In the Na1s spectrum of the DG / MnO-700 sample, a characteristic peak can be clearly observed at 1071.3 eV, indicating that the Na in the manganese dioxide raw material is retained in the DG / MnO-700 sample during the synthesis process (Figure 2 h). Figure 3 is an analysis of the electrochemical performance of the three-dimensional dense graphene / manganese oxide composite material. Figure 3.a shows the first three cycles of cyclic voltammetry test curves of the DG / MnO-700 electrode material with a scan rate of 0.1 mV s -1 , operating voltage is 0.01~3.0 V (vs. Li / Li +). In the first cycle of the cathode scan, two reduction peaks can be observed near 0.5 and 1.4 V, which is due to the formation of a solid electrolyte interface film (SEI) on the electrode surface and the decomposition of the electrolyte during the first cycle of discharge. The disappearance of these two platforms in the subsequent cyclic voltammetry curves indicates that the SEI film formed on the electrode surface is stable. The presence of two characteristic peaks in the anodic scan of DG / MnO-700 may be due to the fact that graphene improves the conductivity of the electrode material and the refinement of MnO grains in the electrochemical reaction promotes the electrochemical kinetics. The fact that the peak current does not decay after cycling indicates that the electrode has good reversibility. The stacking of graphene can protect the MnO particles from being coated with Li2O, thereby improving the conductivity of the electrode material. Figure 3b shows the charge and discharge curves of the DG / MnO-700 sample in the first three cycles at a current density of 100 mA g-1. Two discharge platforms can be observed in the first cycle discharge curve of DG / MnO-700, and two charging platforms can be observed in the charging curve, which is consistent with the CV curve, indicating that the prepared composite material exhibits enhanced kinetics in the reaction. Many previous studies have shown that during the charge and discharge process, the fast Li ion reaction kinetics may be the cause of Mn 2+ In the first discharge cycle, the specific capacity of the DG / MnO-700 electrode is 1645 mAh g -1 , charging capacity is 1039 mAh g -1 The initial Coulombic efficiency was 63.14%. In the second and third charge-discharge cycles, the Coulombic efficiency increased to 93.5% and 94.3%, respectively. Figure 3c shows the rate performance comparison of DG / MnO-700 samples. The DG / MnO-700 electrode exhibits good rate performance due to its unique microstructure. -1 At the charge and discharge current density of 2.5 Å, the reversible capacity of the DG / MnO-700 electrode is 1075 mAh g -1 , while at 2 A g -1 At a current density of 1.34 W, the specific capacity is 703 mAh g -1 Figure 3d shows the rate performance of DG / MnO-700 at high current density. -1 The specific capacity can still be maintained at 327.8 mAh g -1 After charging and discharging at different current densities, when the current density suddenly decreases to 0.5 A g -1 When the specific capacity is 879.1 mAh g -1, indicating that the DG / MnO-700 composite material has good electrochemical reversibility and stability. Figure 3e shows the electrochemical impedance spectrum of the DG / MnO-700 sample. It can be seen from the figure that the semicircle diameter of DG / MnO-700 is the smallest, indicating that its charge transfer rate is the fastest, reflecting the structural superiority of the DG / MnO-700 composite material. Figure 3f shows the current density of 0.5 A g -1 Cyclic stability test curve of DG / MnO-700 electrode at 200 Hz, the tested voltage range is 0.01~3 V (vs. Li / Li + ), during the first few cycles of the test, the specific capacity of the electrode material gradually increased, indicating the gradual activation process of the electrode. After 500 cycles, the specific capacity of the DG / MnO-700 electrode material was still 915.3 mAh g -1 , the capacity retention rate is 101%, showing excellent cycle stability. Figure 3g is the electrochemical impedance spectrum of the DG / MnO-700 electrode material under different cycle numbers. With the increase of the number of cycles, the slope of the low-frequency straight line part of the EIS curve gradually increases, corresponding to the gradual decrease in the lithium ion diffusion resistance in the electrolyte, indicating that the transmission channel of lithium ions gradually becomes unblocked and the migration rate becomes faster during the cycle, which is consistent with the cycle performance curve. Figure 3 h shows the DG / MnO-700 electrode material at 0.1~1 mV s -1 Cyclic voltammetry curves at scan rates. It can be seen that at 1mV s -1 At a high scan rate, the cyclic voltammetry curve of the DG / MnO-700 sample did not change significantly, and the shape and peak position of the curve were similar to those at a low scan rate, indicating that the dense stacked "sandwich" structure of DG / MnO-700 can provide stable charge transfer and ion migration channels for electrochemical reactions, and the conductive network is relatively complete and has good structural stability. The above results show that the three-dimensional dense graphene / manganese oxide (DG / MnO-700) composite material is a promising supercapacitor electrode material.
Claims
1. A three-dimensional dense graphene / manganese oxide composite material is prepared using Na-doped manganese dioxide and graphene as raw materials, and is applied to the negative electrode of a lithium ion battery. The preparation method is carried out according to the following steps:
1. Room temperature synthesis of Na-doped manganese dioxide (MnO2-Na) Weigh 0-140 g of NaCl and dissolve it in 100 mL of deionized water. After vigorous stirring for 30 min, add 0.5 g of KMnO4 to the above solution and stir vigorously for 3 h. Then measure 75 mL of ethanol and slowly add it dropwise to the solution using a separatory funnel. Continue stirring for 30 min. After the reaction is completed, centrifuge and wash immediately until there is no Cl in the system. - (Silver nitrate was used for testing). After sonication, freeze drying was performed and the obtained sample was recorded as MnO2-Na-x (where x corresponds to the amount of NaCl added, in g). The MnO2-Na-x sample was prepared into a dispersion for later use; Preparation of two-dimensional and three-dimensional dense graphene manganese oxide (DG / MnO) 200 mL of GO suspension (0.5 mg / mL) was subjected to strong ultrasound for 10 min, and then ultrasonicated with 100 mL of MnO2 dispersion (containing about 120 mg~350 mg of MnO2) until completely dispersed. The two dispersions were placed in a common ultrasonic water tank, and the MnO2 dispersion was added dropwise to the GO solution (about 5 min) and subjected to strong ultrasound for 10 min. The liquid after ultrasound was evaporated to dryness in a 45°C water bath until about 10 mL of slurry remained. The slurry was applied to a polyethylene plate and dried at room temperature to obtain GO / MnO2 flakes, which were calcined at 600~800°C in a hydrogen atmosphere for 2 h to obtain the sample.
2. The preparation method according to claim 1, characterized in that: The NaCl content in step 1 is 30~100 g.
3. The preparation method according to claim 1, characterized in that The amount of MnO2 added in step 2 is 150 mg~350 mg.
4. The preparation method according to claim 1, characterized in that: Step 2: The calcination temperature is 650~800℃.
Citation Information
Patent Citations
Nitrogen-doped graphene manganese oxide nanowire composite material as well as preparation method and application thereof
CN114899406A
MnO2-loaded graphene aerogel as well as preparation method and application thereof
CN117334891A
A manufacturing method of Na0.44MnO2 nano-rod for an electrode and a manufacturing method sodium rechargeable battery thereof
KR101613435B1